Single Phase Power Generation System from Fuel Cell - Nageswara Rao Kudithi; Sakda Somkun (Institute of Advanced Engineering and Science, 2018)
Power conditioning circuits are required for the fuel cell systems due to its nature in energetic state. This paper proposed the small signal average modelling of a duel active bridge (DAB) DC-DC converter with LC filter, to generate the single phase AC power by using the H1000 fuel cell system. The controller is designed for the stable operation of the system. Implemented the controller, which gives the constant output voltage to DC-bus from the DAB DC-DC converter, this DC-bus voltage fed to the inverter, which inverts the DC-bus voltage to single Phase AC power with the LC-filter. The proposed system simulated in the MATLAB/Simulink.